Supplier management: past, present and anticipated future perspectives. (1st May 2007) - Phusavat, Kongkiti; Kanchana, Rapee; Helo, Petri
The study illustrates the historical development of the criteria used for supplier management, and suggests a possible future trend as a result of this development. This study stems from globalisation in the private sector, and many policy initiatives of Thai public agencies to assist specific industries, such as electronic and automotive sectors. The awareness of these past and current developments, coupled with anticipation of a possible future trend, should help large companies and Small and Medium Enterprises (SMEs) become better prepared. This study initially relies on literature reviews for identifying the criteria's historical development, and later confirms the result with separate surveys to companies belonging to the Federation of Thai Industries (FTI). A future trend on accreditation practices is suggested and discussed. This is potentially useful for value chain management, especially for SMEs when dealing with large companies. The follow-up discussion seems to agree with this suggestion.